1998
DOI: 10.1046/j.1365-2605.1998.00131.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical expression of monoclonal antibody 43‐9F in testicular germ cell tumours

Abstract: The aim of this study was to evaluate the clinical utility of immunohistochemical staining of human testicular germ cell tumours with the monoclonal antibody 43-9F to distinguish embryonal carcinoma (EC) from other malignant germ cell components in order to facilitate pathohistological assessment of prognostic risk factors for metastatic disease in clinical stage I NSGCT. Archival, formalin-fixed, paraffin-embedded tissue blocks of 24 classical seminomas, 7 spermatocytic seminomas, and 20 non-seminomatous germ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…Interestingly, the putative nonmalignant counterpart of carcinoma in situ has been suggested to be present around the 9th to 10th week of intrauterine development (Jørgensen et al, 1995), which would be in accordance with our present findings. This is also in agreement with epidemiological data (Adami et al, 1994), immunohistochemical findings (Cummings et al, 1994;Heidenreich et al, 1998;Hittmair et al, 1996;Rajpert-De Meyts and Skakkebaek, 1994;Roelofs et al, 1999), and expression analysis of human endogenous retrovirus K (HERV-K)-specific transcripts (Herbst et al, 1999;Roelofs et al, 1998). These markers are overall negative in normal spermatogenesis and spermatocytic seminomas, and positive in TGCTs.…”
Section: Stoop Et Alsupporting
confidence: 89%
“…Interestingly, the putative nonmalignant counterpart of carcinoma in situ has been suggested to be present around the 9th to 10th week of intrauterine development (Jørgensen et al, 1995), which would be in accordance with our present findings. This is also in agreement with epidemiological data (Adami et al, 1994), immunohistochemical findings (Cummings et al, 1994;Heidenreich et al, 1998;Hittmair et al, 1996;Rajpert-De Meyts and Skakkebaek, 1994;Roelofs et al, 1999), and expression analysis of human endogenous retrovirus K (HERV-K)-specific transcripts (Herbst et al, 1999;Roelofs et al, 1998). These markers are overall negative in normal spermatogenesis and spermatocytic seminomas, and positive in TGCTs.…”
Section: Stoop Et Alsupporting
confidence: 89%
“…Prior studies have found a wide spectrum of positivity of AFP, from 55% to 100%, with authors noting that focal reactivity can limit the utility of the marker 18,29–33 . Furthermore, AFP has been reported to stain embryonal carcinoma; in over half of cases in some studies 30,31,33,34 . These issues have led some authors to conclude that AFP is not a specific or reliable marker for YST 29,34 …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, AFP has been reported to stain embryonal carcinoma; in over half of cases in some studies 30,31,33,34 . These issues have led some authors to conclude that AFP is not a specific or reliable marker for YST 29,34 …”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies identified a number of antigens that were highly expressed in CIS cells and gonocytes but not in the normal germ cell in the adult testes. Other CIS markers were identified using antibodies raised against glycolipids and glycoproteins expressed by tumour-derived cell lines, including M2A (22,(30)(31)(32), 43-9F (22,33,34) and TRA-1-60 (35). One of the first markers found was placental-like alkaline phosphatase (PLAP), a tissue-specific alkaline phosphatase with unknown biological function, which is also expressed in classical seminoma as well as primordial germ cells and early gonocytes (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26).…”
Section: Similarities Between Cis Cells and Normal Germ Cellsmentioning
confidence: 99%